A high-throughput assay for screening natural products that boost NK cell-mediated killing of cancer cells. (1st January 2020) - Xu, Zihang; Zhu, Xiaowen; Su, Lin; Zou, Chunpu; Chen, Xiao; Hou, Yifei; Gong, Chenyuan; Ng, Wanyi; Ni, Zhongya; Wang, Lixin; Yan, Xuewei; Zhu, Yangzhuangzhuang; et al.
Abstract: Context: Natural killer (NK) cells can eliminate malignant cells and play a vital role in immunosurveillance. Administration of natural compounds represents a promising approach for antitumor immunotherapy, which may enhance the NK cell activity via multiple mechanisms. Objective: Establishing approaches to evaluate the effect of select natural products on NK cell-mediated cytotoxicity. Materials and methods: We selected a natural product library containing 2880 pure compounds, which was provided by the National Centre for Drug Screening of China. 0.1% DMSO was employed as a negative control, and 100 U/mL human recombinant IL-2 was employed as a positive control. To evaluate the % of tumour cells which were killed by NK cells, expanded NK cells were co-cultured with tumour cells and then treated with natural products at the concentration of 10 μM. After 24-h co-incubation, luminescent signal was detected and percent lysis was calculated. Results: We report on the results of a three-round high-throughput screening effort that identified 20-deoxyingenol 3-angelate (DI3A) and its analogue ingenol 3-angelate (I3A) as immuno enhancers which boosts NK cell-mediated killing of non-small cell lung cancer cells (NSCLCs). Biophotonic cytotoxicity assay and calcein release assay were used as two well-established NK cell cytotoxicity detection assays to validate the immuno-enhancing effects of DI3A and I3A, which was achieved by increasing degranulation and interferon-gamma secretion of NK cells. Conclusions: Our newly established ATP-based method was a valuable and information-rich screening tool to investigate the biological effects of natural products on both NK cells and tumour cells.